Haydn and the Performance of Rhetoric - Beghin, Tom; Goldberg, Sander M. (Chicago, IL University of Chicago Press, 2007)
Haydn is the last major composer whose music was regularly discussed by his contemporaries in terms derived from the classical tradition of rhetoric. Within a generation of his death, that discourse had fallen from favor, but the historical relationship between Haydn and the rhetorical tradition endured. In this volume, a distinguished group of contributors in fields from classics to literature to musicology restores the rhetorical model to prominence and shows what can be achieved by returning to the idea of music as a rhetorical process. An accompanying DVD, specially designed for this project, presents performances and illustrations keyed to its chapters, making musicological arguments accessible to nonspecialists and advancing additional arguments of its own through the medium of performance. The volume thus reaches beyond musicology to enrich and complicate the larger debate over rhetoric's role in eighteenth-century culture.
Keywords: Haydn, Joseph -- 1732-1809; Rhetoric; Performance